1992
DOI: 10.1111/j.1476-5381.1992.tb14258.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary treatment with essential fatty acids on sciatic nerve conduction and activity of the Na+/K+ pump in streptozotocin‐diabetic rats

Abstract: 1 This study examined the effects of dietary essential fatty acid supplementation (5% (w/w) evening primrose oil) upon sciatic motor nerve conduction velocity and 86Rb+ pumping in sciatic nerve endoneurial preparations in rats with 4 to 5 weeks of streptozotocin-induced diabetes. 2 Control diabetic rats (dietary supplementation with 5% (w/w) hydrogenated coconut oil) exhibited a reduction in motor nerve conduction velocity (16%; P < 0.05) compared to similarly-fed non-diabetic controls, but there was no signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Thus, the vascular effects of EPO and ARI treatments can be identified with increased prostacyclin and NO action respectively, although this may be an oversimplification since ARI treatment partially corrected reduced aorta prostacyclin output [29] and a deficit in the pressor response to arachidonic acid [30] in diabetic rats. No effects of EPO on polyol pathway metabolites were observed, in agreement with previous findings [31,32].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, the vascular effects of EPO and ARI treatments can be identified with increased prostacyclin and NO action respectively, although this may be an oversimplification since ARI treatment partially corrected reduced aorta prostacyclin output [29] and a deficit in the pressor response to arachidonic acid [30] in diabetic rats. No effects of EPO on polyol pathway metabolites were observed, in agreement with previous findings [31,32].…”
Section: Discussionsupporting
confidence: 82%
“…Taken together, these data suggest that a myo-inositol/Na-K ATPase mechanism is unlikely to contribute to the NCV or blood flow results. Furthermore, NCV deficits are corrected by vasodilator or EPO treatments that do not alter Na-K ATPase activity [32,39] and ARI/myo-inositol effects on Na-K ATPase are only found in rats fed a high sucrose diet [4O].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the reduced sciatic nerve laser Doppler flux in diabetic rats indicates possible ischaemia and that a high dose of evening primrose oil has the potential to prevent nerve ischaemia and conduction abnormalities [5,40]. We also reported that evening primrose oil treatment increases tissue prostacyclin production [9].…”
Section: Discussionmentioning
confidence: 69%
“…In other studies, pathways involving the metabolism of arachidonic acid could also be involved in mediating changes in vascular reactivity. Supplementing diabetic rats with γ‐linolenic acid, an arachidonic acid precursor, has been shown to improve motor nerve conduction velocity and neuronal blood flow in the sciatic nerve (Lockett & Tomlinson, 1992; Karasu et al ., 1995; Cameron et al ., 1996; Cotter & Cameron, 1997). Furthermore, the prostacyclin analogue beraprost sodium has been shown to increase sciatic nerve blood flow in diabetic rats (Hotta et al ., 1996).…”
Section: Discussionmentioning
confidence: 99%